Bifunctional Electrocatalysts: ZIF‐8/ZIF‐67‐Derived Co‐Nx‐Embedded 1D Porous Carbon Nanofibers with Graphitic Carbon‐Encased Co Nanoparticles as an Efficient Bifunctional Electrocatalyst (Small 24/2018). Issue 24 (14th June 2018) - Zhang, Wenming; Yao, Xiuyun; Zhou, Shengnan; Li, Xiaowei; Li, Ling; Yu, Ze; Gu, Lin
Abstract : In article number1800423, Ling Li, Ze Yu, Lin Gu, and co‐workers use ZIF‐8/ZIF‐67 with electrospinning to successfully fabricate Co‐N x ‐embedded 1D porous carbon nanofibers. The unique 1D structure, such as higher graphitization degree beneficial, hierarchical porosity, and highly dispersed CoN x C active sites, is beneficial for highly efficient electrochemical performance for oxygen reduction and oxygen evolution reactions.